2006
DOI: 10.1111/j.1365-3156.2006.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for health insurance in Rwanda: who should pay how much?

Abstract: SummaryCommunity-based health insurance schemes were introduced in Rwanda in 1999 and now cover 27% of the population. Due to widespread poverty, it remains unclear to what degree poorer population strata can be anticipated to pay into the system. This study investigates the extent to which the Rwandan population can financially contribute to obtain health insurance. More specifically, researchers explored the relationship between resource mobilization for the health system and the ability to provide community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…They could dialogue with the communities, scheme staff and the providers to improve enrolment in the plans. Subsidies to the poorest members of the community could increase enrolment and thus access to care [22,23]. More importantly, donors and governments could finance research/projects that test different approaches to extending insurance to the poorest [24].…”
Section: Resultsmentioning
confidence: 99%
“…They could dialogue with the communities, scheme staff and the providers to improve enrolment in the plans. Subsidies to the poorest members of the community could increase enrolment and thus access to care [22,23]. More importantly, donors and governments could finance research/projects that test different approaches to extending insurance to the poorest [24].…”
Section: Resultsmentioning
confidence: 99%
“…This example has been suggested to ensure that the poor and other vulnerable groups of the populace are covered. 45,46 Limitations. Expressed concerns of participants about prepayment schemes could not be discussed deeply because of the quantitative nature of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average Rwandan population will be incapable to raise these resources. Schmidt et al. (2006) found that only 75% of the Rwandan population could afford to pay insurance premiums of 1 US$ per capita per year.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average Rwandan population will be incapable to raise these resources. Schmidt et al (2006) found that only 75% of the Rwandan population could afford to pay insurance premiums of 1 US$ per capita per year. Their results imply that current premiums of 1.75 US$ already exceed the contributory capacity of more than 25% of Rwandan households.…”
Section: Element 7: Nutrition Supportmentioning
confidence: 99%